2021
DOI: 10.1371/journal.pone.0246571
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and interspecies gene transfer in Campylobacter coli and Campylobacter jejuni isolated from food animals, poultry processing, and retail meat in North Carolina, 2018–2019

Abstract: The Center for Disease Control and Prevention identifies antimicrobial resistant (AMR) Campylobacter as a serious threat to U.S. public health due to high community burden, increased transmissibility, and limited treatability. The National Antimicrobial Resistance Monitoring System (NARMS) plays an important role in surveillance of AMR bacterial pathogens in humans, food animals and retail meats. This study investigated C. coli and C. jejuni from live food animals, poultry carcasses at production, and retail m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 53 publications
6
27
1
Order By: Relevance
“…Campylobacter isolates showed MDR (57.3%) to aminoglycosides, tetracycline, and penicillin ( Table 3 ). This is higher than previous reports in North Carolina and southeastern US [ 103 , 109 ]. The resistance of Campylobacter isolates to Tet (63%), Cli (11.7%), Gen (25%), Kan (48.5%), and Str (22%) in this study is higher than the detected prevalence in the midwestern and northeastern US [ 110 , 111 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Campylobacter isolates showed MDR (57.3%) to aminoglycosides, tetracycline, and penicillin ( Table 3 ). This is higher than previous reports in North Carolina and southeastern US [ 103 , 109 ]. The resistance of Campylobacter isolates to Tet (63%), Cli (11.7%), Gen (25%), Kan (48.5%), and Str (22%) in this study is higher than the detected prevalence in the midwestern and northeastern US [ 110 , 111 ].…”
Section: Discussioncontrasting
confidence: 67%
“…Though the phenotypic resistance was not determined against penicillin in the current study, some strains of Campylobacter appear to have bla OXA gene variants, highlighting the potential role of the wild birds in the transmission of β-lactam resistance genes. Hull et al (2021) recently showed the high prevalence of β-lactam antimicrobial resistance genes including bla OXA variants among C. coli and C. jejuni strains from live food animals and retail meats.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of genome assembly was assessed using Quast [50]. AMR genes, plasmids, and virulence genes were identified by the ABRicate pipeline, as previously described [51]. ABRicate included multiple databases including NCBI, CARD, ARG-ANNOT, ResFinder, MEGARES, EcOH, PlasmidFinder, Ecoli_VF, and VFDB.…”
Section: Whole-genome Sequencingmentioning
confidence: 99%